VO.02 - Final valuation of waterprooﬁng on the retaining wall and capping beam - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding the VO.02 - final valuation of waterprooﬁng on the retaining wall and capping beam of Brac University new campus development project .